2008
DOI: 10.1021/ja076529e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mg2+ in Hammerhead Ribozyme Catalysis from Molecular Simulation

Abstract: Molecular dynamics simulations have been performed to investigate the role of Mg 2+ in the fulllength hammerhead ribozyme cleavage reaction. In particular, the aim of this work is to characterize the binding mode and conformational events that give rise to catalytically active conformations and stabilization of the transition state. Toward this end, a series of eight 12 ns molecular dynamics simulations have been performed with different divalent metal binding occupations for the reactant, early and late trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
137
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 75 publications
(160 reference statements)
13
137
0
Order By: Relevance
“…7D). The same trend is seen in the in-line fitness parameter (Soukup and Breaker 1999;Lee et al 2008), which includes both the IAA and the O29-P attack distance (Fig. 7D, inset).…”
Section: Cf Sch-nol and Sch-wt)supporting
confidence: 68%
“…7D). The same trend is seen in the in-line fitness parameter (Soukup and Breaker 1999;Lee et al 2008), which includes both the IAA and the O29-P attack distance (Fig. 7D, inset).…”
Section: Cf Sch-nol and Sch-wt)supporting
confidence: 68%
“…High-resolution crystal structures exist for the HDV (Ke et al 2004(Ke et al , 2007, hammerhead (Martick and Scott 2006;Lee et al 2008), glmS (Klein and Ferré-D'Amaré 2006;Cochrane et al 2007), and hairpin ribozymes (Rupert and Ferré-D'Amaré 2001;Rupert et al 2002;Alam et al 2005;Salter et al 2006;Torelli et al 2007;MacElrevey et al 2008;Torelli et al 2008). Based on these structures only the hairpin ribozyme's active site is unambiguously devoid of stably bound metal ions that could potentially participate in catalysis with the possible exception of electrostatic stabilization, which could influence chemistry from outside the active site.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous study identified an apparent increase in Mg 2+ -binding affinity to HH(S) in mixed solutions with a low dielectric constant [34,35]. The substrate cleavage catalyzed by the hammerhead ribozyme requires the involvement of several Mg 2+ ions, and at least one Mg 2+ ion binds to the site with highly negative electrostatic potential located near the scissile phosphate of the substrate [49]. This mechanism is consistent with the dielectric constant effect that facilitates electrostatic Mg 2+ binding and allows greater enhancement of the turnover activity observed at the low Mg 2+ concentration of 1 mM.…”
Section: Effects On the Hammerhead Ribozymementioning
confidence: 97%